Plastic bronchitis: a clinical case - M.O. Gonchar; G.R. Muratov; O.L. Logvinova; Y.M. Pushkar; N.N. Iyblonska; V.V. Kostenko; S.B. Dolgareva (Zaslavsky O.Yu., 2018)
The publication is devoted to the in-depth consideration of etiology, pathogenesis, diagnosis and treatment of a rare disease of the bronchi - plastic bronchitis. Plastic bronchitis is more common in children with congenital heart disease after a Fonten palliative surgery (1-4 %), rarely is induced by the surgery for the Fallot's tetralogy, postoperative chylothorax or ascites, reconstructive operations; as well as bronchiectasis, bronchial asthma, tuberculosis, cystic fibrosis, chronic bronchitis, lung transplantation, H1N1 flu, heart failure, rheumatoid arthritis, or amyloidosis. The idea of writing the article arose during the clinical observation of a five-year-old girl who was hospitalized with manifested progressive hypoxia, shortness of breath and obsessive paroxysmal cough; the bronchoscopy found plastic casts. The diagnostic search for a disease for which this type of casts is typical has shown limited information in world literature sources. We did not find Ukrainian-language publications devoted to this disease. The authors review the modern world literature, consider the criteria for diagnosis, modern classification system of plastic bronchitis, based on the histology of casts; the effective methods of diagnostics and differential diagnostics of diseases factors of plastic bronchitis. Clinical observation is illustrated with images of bronchial casts, results of X-ray and computed tomography of the lungs in spiral mode with a 3 mm step with multiplanar reconstruction, which from our point of view can complement the knowledge bank of pediatricians, pediatric pulmonologists, thoracic surgeons, as well as cardiac surgeons and cardiologists in Ukraine.